Oral manifestations of patients with systemic sclerosis: a meta-analysis for case-controlled studies - Suhan Zhang; Junfei Zhu; Yanshan Zhu; Xiaochao Zhang; Ruifang Wu; Siying Li; Yuwen Su (BMC, 2021)
Abstract Background Systemic sclerosis (SSc) is a multisystem rheumatic disease. Orofacial manifestations are commonly in SSc but maybe usually ignored and overshadowed by other systemic complications. Multiple comparative studies have been conducted to investigate the possible links between SSc and oral manifestations. The present study aimed to investigate the oral health status in patients with SSc. Methods Pubmed, Embase, Web of Science, and Scopus were searched up to July 2020. Following outcomes were evaluated: Probing depth (PD), Attachment loss (AL), Bleeding on probing (BOP), Number or percentage of Sites with PD ≥ 4 mm, Prevalence of periodontitis, Number of teeth, Decayed Teeth, Missing teeth, Filled teeth, DMFT index, and the interincisal distance. Newcastle-Ottawa Scale (NOS) were applied for quality assessment. The statistical analysis was processed using the software STATA. Results 11 eligible studies were included. The maximum interincisor distance was significantly restricted in SSc patients (SMD − 1.061; 95 %CI [− 1.546, − 0.576]; Z = 4.29, P = 0.000).The prevalence of Periodontitis (OR 7.007; 95 %CI [3.529, 13.915]; Z = 5.56, P = 0.000), PD (SMD 3.101; 95 %CI [1.374, 4.829]; Z = 3.52, P = 0.000), AL(SMD 2.584; 95 %CI [0.321, 4.846]; Z = 2.24, P = 0.025), sites with PD ≥ 4mm (SMD 2.071 ; 95 %CI [0.267, 3.875]; Z = 2.25, P = 0.024) and the number of decayed teeth (SMD, 0.186; 95 %CI [0.007, 0.365]; Z = 2.04, P = 0.041) were increased significantly in SSc population in comparison with the controls. Conclusions SSc patients have limited mouth opening, higher periodontitis prevalence, and worse periodontal status, as well as an increased number of decayed teeth. Routinely oral hygiene instruction and initial periodontal treatment is recommended for SSc patients.